Effects of algorithm for diagnosis of active labour: cluster randomised trial. (8th December 2008) - Cheyne, Helen; Hundley, Vanora; Dowding, Dawn; Bland, J Martin; McNamee, Paul; Greer, Ian; Styles, Maggie; Barnett, Carol A; Scotland, Graham; Niven, Catherine
Abstract : Objective To compare the effectiveness of an algorithm for diagnosis of active labour in primiparous women with standard care in terms of maternal and neonatal outcomes. Design Cluster randomised trial. Setting Maternity units in Scotland with at least 800 annual births. Participants 4503 women giving birth for the first time, in 14 maternity units. Seven experimental clusters collected data from a baseline sample of 1029 women and a post-implementation sample of 896 women. The seven control clusters had a baseline sample of 1291 women and a post-implementation sample of 1287 women. Intervention Use of an algorithm by midwives to assist their diagnosis of active labour, compared with standard care. Main outcomes Primary outcome: use of oxytocin for augmentation of labour. Secondary outcomes: medical interventions in labour, admission management, and birth outcome. Results No significant difference was found between groups in percentage use of oxytocin for augmentation of labour (experimental minus control, difference=0.3, 95% confidence interval −9.2 to 9.8; P=0.9) or in the use of medical interventions in labour. Women in the algorithm group were more likely to be discharged from the labour suite after their first labour assessment (difference=−19.2, −29.9 to −8.6; P=0.002) and to have more pre-labour admissions (0.29, 0.04 to 0.55; P=0.03). Conclusions Use of an algorithm to assist midwives with the diagnosis of active labour in primiparous women did not result in a reduction in oxytocin use or in medical intervention in spontaneous labour. Significantly more women in the experimental group were discharged home after their first labour ward assessment. Trial registration Current Controlled Trials ISRCTN00522952 .